Conifer species influence Heterobasidion irregulare sporulation on stem discs exposed to natural inoculum and root wood decay in soil‐block tests. Issue 1 (7th September 2017) - Ohno, K.; Myers, L. J.; Smith, D. R.; Clausen, C. A.; Mausel, D.; Stanosz, G. R.
Summary: The fungal pathogen Heterobasidion irregulare has caused substantial damage to pine species in much of the south‐eastern United States, but the potential for damage from Heterobasidion root disease to forest tree species of the Great Lakes Region has not been thoroughly investigated. In each of three trials in two infested stands, fresh stem discs of six native conifer species were exposed to natural inoculum and examined for the asexual Spiniger stage of H. irregulare after incubation in the laboratory. In the first trial, the fungus was infrequently observed on discs, and differences among species were not found. But in the other two trials, detection of the pathogen was much more frequent on discs of tamarack ( Larix laricina ), red pine ( Pinus resinosa ) and white spruce ( Picea glauca ) than those of northern white cedar ( Thuja occidentalis ), eastern hemlock ( Tsuga canadensis ) and balsam fir ( Abies balsamea ). In a second study, the ability of an isolate of H. irregulare to decay root sapwood of these same species was compared using a soil‐block decay test. After 16 weeks of incubation, weight loss due to decay was greatest for red pine (23.2%) and larch (19.1%) and least for balsam fir (1.3%). Differences in the ability of H. irregulare to infect and saprophytically utilize substrate of these important tree species should prompt additional investigation of the relative risk posed to forests of the Great Lakes Region.